2009
DOI: 10.1177/0040517508099921
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Seam Strength of Notched Webbings for Parachute Assemblies Using the Taguchi's Design of Experiment and Artificial Neural Networks

Abstract: Webbings are used in parachute assemblies as reinforcing units for the strength they provide. The strength of these seams is an important characteristic which has a substantial influence on the mechanical property of the parachute assemblies. It is well established that factors such as fabric width, folding length of joint, seam design and seam type will all have an impact on seam strength. In this work, the effect of these factors on seam strength was studied using both Taguchi's design of experiment (TDOE) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 21 publications
0
14
0
Order By: Relevance
“…The validation of the Taguchi's method was not ensured in most of the earlier studies Kumar et al, 2006aKumar et al, , 2006bKumar et al, , 2006cSalhotra et al, 2006) and the relative difference was observed to be very high, which was up to 42% in few of the studies (Onal, Zeydan, Korkmaz, & Meeran, 2009). To ensure the efficiency of prediction of Taguchi's method, eighteen different multilayered fabrics were validated in this study.…”
Section: Validation Of Taguchi's Methodsmentioning
confidence: 96%
“…The validation of the Taguchi's method was not ensured in most of the earlier studies Kumar et al, 2006aKumar et al, , 2006bKumar et al, , 2006cSalhotra et al, 2006) and the relative difference was observed to be very high, which was up to 42% in few of the studies (Onal, Zeydan, Korkmaz, & Meeran, 2009). To ensure the efficiency of prediction of Taguchi's method, eighteen different multilayered fabrics were validated in this study.…”
Section: Validation Of Taguchi's Methodsmentioning
confidence: 96%
“…After that, the final weights and biases can be arrived at. The output value will be close to the target value [23,24]. The criterion for the error function adopted in the network is as follows: (7) where T j and Y j respectively represent the target output and the predicted output of jth output neuron in the output layer.…”
Section: Back Propagation Neural Networkmentioning
confidence: 99%
“…Therefore, both models were effectively predicting the seam performance of woven fabrics. Onal et al, (2009) studied the effect of factors on seam strength of webbings made from polyamide 6.6 which were used in parachute assemblies as reinforcing units for providing strength by using both Taguchi's design of experiment (TDOE) as well as an artificial neural network (ANN), then compared them with the strength physically obtained from mechanical tests on notched webbing specimens. It was established from these comparisons, in which the root mean square error was used as an accuracy measure, that the predictions by ANN were better predictions of the experimental seam strength of jointed notched webbing in accuracy than those predicted by TDOE.…”
Section: Applications To Fabricsmentioning
confidence: 99%